2010
DOI: 10.1250/ast.31.394
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of emotion perception among different cultures

Abstract: In this study, we conducted a comparative experiment on emotion perception among different cultures. Emotional components were perceived by subjects from Japan, the United States and China, all of whom had no experience living abroad. An emotional speech database without linguistic information was used in this study and evaluated using three-and/or six-emotional dimensions. Principal component analysis (PCA) indicates that the common factors could explain about 60% variance of the data among the three cultures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…In actuality, emotions are complex and often there is no single emotion expressed in an utterance (see e.g., Dang et al 2010). Moreover, the emotional labels used can lead to confusing results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In actuality, emotions are complex and often there is no single emotion expressed in an utterance (see e.g., Dang et al 2010). Moreover, the emotional labels used can lead to confusing results.…”
Section: Discussionmentioning
confidence: 99%
“…However, even with spontaneous emotional expressions (Erickson et al 2006;Spring et al 1992) or professionally-acted emotions (e.g., Dang et al 2010), not all utterances are perceived as the emotion intended by the speaker. A related theoretical question along these lines is whether emotions are expressed to be communicated to others (Ohala 1994), which predicts that particular emotions should have particular acoustic targets, or are they part of a human's cathartic system, produced to bring about relief to one's intense emotional experiencing of pain, pleasure, fear, sorrow, etc.…”
Section: The Current Studymentioning
confidence: 99%
“…It is reported that female listeners are more sensitive to emotion than males [22]. The perception also depends on culture [23]. Even though listener variability affects the majority decision as to emotion perception, there is little work that considers the listener in SER.…”
Section: I R E L a T E D W O R Kmentioning
confidence: 99%
“…is similar in emotion perceptions, and depends on age [21], gender [22], and cultures [23] of listeners. Given these issues, speaker dependency has often been considered for SER [24,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation